Anion–π Catalysis of Diels–Alder Reactions. Issue 42 (8th September 2017) - Liu, Le; Cotelle, Yoann; Bornhof, Anna‐Bea; Besnard, Céline; Sakai, Naomi; Matile, Stefan
Abstract: Among concerted cycloadditions, the Diels–Alder reaction is the grand old classic, which is usually achieved with acid catalysis. In this report, hydroxypyrones, oxa‐, and thiazolones are explored because they provide access to anionic dienes. Their [4+2] cycloaddition with cyclic and acyclic dienophiles, such as maleimides and fumarates, affords bicyclic products with four new stereogenic centers. Bifunctional anion–π catalysts composed of amine bases next to the π surface of naphthalenediimides (NDIs) are shown to selectively stabilize the "open", fully accessible anionic exo transition state on the π‐acidic aromatic surface. Our results also include reactivities that are hard to access with conventional organocatalysts, such as the exo ‐specific and highly enantioselective Diels–Alder reaction of thiazolones and maleimides with complete suppression of the otherwise dominant Michael addition. With increasing π acidity of the anion–π catalysts, the rates, chemo‐, diastereo‐, and enantioselectivities increase consistently. Abstract : The grand old classic dancing on π‐acidic surfaces finally enables otherwise elusive reactivity. For example, the endo / exo diastereoselectivity of the Diels–Alder reaction of hydroxypyrones with fumarates was inverted, and the enantioselective [4+2] cycloaddition of thiazolones and maleimides proceeded with exo specificity without a trace of the otherwise preferred Michael addition product.